Status of Treatment and Prophylaxis for Radiation-Induced Oral Mucositis in Patients With Head and Neck Cancer - Liu, Shiyu; Zhao, Qin; Zheng, Zhuangzhuang; Liu, Zijing; Meng, Lingbin; Dong, Lihua; Jiang, Xin (Frontiers in Oncology, 2021)
Radiation-induced oral mucositis (RIOM) is one of the most frequent complications in head and neck cancer (HNC) patients undergoing radiotherapy (RT). It is a type of mucosal injury associated with severe pain, dysphagia, and other symptoms, which leads to the interruption of RT and other treatments. Factors affecting RIOM include individual characteristics of HNC patients, concurrent chemoradiation therapy, and RT regimen, among others. The pathogenesis of RIOM is not yet fully understood; however, the release of inflammatory transmitters plays an important role in the occurrence and development of RIOM. The five biological stages, including initiation, primary damage response, signal amplification, ulceration, and healing, are widely used to describe the pathophysiology of RIOM. Moreover, RIOM has a dismal outcome with limited treatment options. This review will discuss the epidemiology, pathogenesis, clinical appearance, symptomatic treatments, and preventive measures related to this disease. We hope to provide a reference for the clinical treatment and prevention of RIOM in HNC patients after RT.